Recent advances in radionuclide medical imaging techniques - Xu, Shuyu; Liu, Ge; Wei, Qingyang; Liu, Hui; Wu, Jing; Liu, Yaqiang; He, Zuo-Xiang (Frontiers in Medicine, 2025)
Radionuclide imaging combines nuclear technique and medicine through the administration of radioactive drugs into living organisms, followed by imaging with specialized instruments. This technique is essential in modern medicine, facilitating diagnosis, treatment, medical research, exploration of drug mechanisms, and evaluation of drug efficacy. This review critically synthesizes the pivotal advancements in the field over the past decade, moving beyond a descriptive overview to analyze the clinical impact and translational barriers of emerging technologies. We evaluate key innovations in traditional modalities, such as the role of CZT detectors in transforming cardiac SPECT and the impact of TOF and DOI on quantitative accuracy in PET. Furthermore, we provide a comparative analysis of multimodal systems (e.g., PET/CT vs. PET/MRI), focusing on their clinical decision-making context. Emerging paradigms like self-collimation and cascade gamma photon imaging are examined as potential solutions to the inherent limitations of current systems, with a critical assessment of their technology readiness levels. A significant focus is placed on the rapidly evolving landscape of theranostics, highlighting the synergy between imaging and targeted radionuclide therapy. By identifying key trends, persistent challenges, and future directions, this review provides a comprehensive and critical perspective on the ongoing evolution of radionuclide imaging from a technological and clinical standpoint.